2001
DOI: 10.1021/ie010439f
|View full text |Cite
|
Sign up to set email alerts
|

Production of Valuable Materials by Hydrothermal Treatment of Shrimp Shells

Abstract: The possibility of amino acids and glucosamine production from the treatment of shrimp shells in high-temperature and high-pressure water was investigated. Under the tested conditions, the highest amount of amino acids (70 mg/g of dry shrimp shell) from hydrolysis of proteins was obtained at a reaction temperature of 523 K in 60 min. This amount was about 2.5 times the total amino acids obtained at 363 K, the temperature at which shrimp extracts for use in noodles soup are being prepared. The amount of simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 11 publications
(18 reference statements)
3
54
0
3
Order By: Relevance
“…The difference compared to our results may be due to the different sample processing and experimental conditions. Other studies works reported that the thermal degradation of amino acids occurs at temperatures above 250 to 300°C, depending on the raw protein material and corresponding contact time Quitain et al, 2001;Yoshida et al, 2003).…”
Section: Composition Of Heat-dried Squid Visceramentioning
confidence: 99%
“…The difference compared to our results may be due to the different sample processing and experimental conditions. Other studies works reported that the thermal degradation of amino acids occurs at temperatures above 250 to 300°C, depending on the raw protein material and corresponding contact time Quitain et al, 2001;Yoshida et al, 2003).…”
Section: Composition Of Heat-dried Squid Visceramentioning
confidence: 99%
“…It may be differ due to the different sample sources, processing and experimental operational conditions. Some other works have been carried out in which the thermal degradation of amino acids occur at temperature above 250 to 300°C, depending on the raw protein and corresponding contact time Quitain et al 2001;Yoshida et al 2003).…”
Section: Sds-pagementioning
confidence: 99%
“…In addition, collapse of krill shell material could become increasingly important at elevated temperatures, facilitating lipid extraction. Chitosan and protein, which are the shell components of the crustacean organism (22), could be decomposed by subcritical water hydrolysis (23).…”
Section: Lipid Contentmentioning
confidence: 99%